2009
DOI: 10.1021/jp904374h
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Enantioselectivity of Chiral N-Linked Peptidoresorc[4]arene Isomers toward Dipeptides

Abstract: The gas-phase enantioselectivity of cone N-linked peptidoresorc[4]arenes (generally symbolized as M) toward the homologue dipeptides (generally symbolized as A) has been evaluated by measuring the kinetics of the A release from the diastereomeric [M x H x A](+) complexes induced by (R)-(-)-2-butylamine (B). In most cases investigated, the heterochiral [M x H x A](+) complexes, namely those wherein the configuration of the A guest is opposite to that of the host M pendants, react faster (up to 5 times) than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…These preliminary results motivated the gas-phase enantioselectivity study reported in [43], in which the guest displacement between proton-bound diastereomeric [ M ∙H∙G] + ( M : I – IV ; G = 1 – 3 ) complexes and ( R )-(−)-2-butylamine (B) (Eq. 5 and Eq.…”
Section: Reviewsupporting
confidence: 74%
See 4 more Smart Citations
“…These preliminary results motivated the gas-phase enantioselectivity study reported in [43], in which the guest displacement between proton-bound diastereomeric [ M ∙H∙G] + ( M : I – IV ; G = 1 – 3 ) complexes and ( R )-(−)-2-butylamine (B) (Eq. 5 and Eq.…”
Section: Reviewsupporting
confidence: 74%
“…The resorcin[4]arene octamethyl ethers were functionalized with leucyl-valine and valyl-leucine ( I and III ; Scheme 1) methyl esters, and the enantioselectivity toward the same dipeptide esters used in their synthesis, namely, leucyl-valine-OMe and valyl-leucine-OMe ( 1 and 3 ; Scheme 1) was investigated [43]. …”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations